EVALUATION OF RADIOLOGICAL SIGNIFICANCE OF RARE-EARTH METALS WITH NATURAL RADIOACTIVE ISOTOPES - E. P. Lisachenko (Радиационная гигиена)
Among the rare-earth metals with natural radioactive isotopes, lantan, lutetium and samarium are allocated a relatively high specific activity. The formation of the additional external radiation keep it close to the significance of the materials to the radiation categories of materials with a high content of natural radionuclides of uranium and thorium family, lanthanum value is much less. Samarium, with acceptable toxicology content in the working area, forms the internal exposure to the limits for professionals. The use of these elements in science and industry requires the radiation-hygienic evaluation.